Library Association record. - Guppy, Henry, 1861-1948; Esdaile, Arundell James Kennedy, 1880-1956
Proceedings of the 22d-33d annual conference of the Library Association in v. 1-12; proceedings of the 34th-44th, 47th-57th annual conference issued as a supplement to v. 13-23, new ser. v. 3-ser. 4, v. 1.